2007
DOI: 10.1021/bi7016975
|View full text |Cite
|
Sign up to set email alerts
|

A Flavin-Dependent Sulfhydryl Oxidase in Bovine Milk

Abstract: Both metal and flavin-dependent sulfhydryl oxidases catalyze the net generation of disulfide bonds with the reduction of oxygen to hydrogen peroxide. The first mammalian sulfhydryl oxidase to be described was an iron-dependent enzyme isolated from bovine milk whey (Janolino, V.G., and Swaisgood, H.E. (1975) J. Biol. Chem. 250, 2532-2537). This protein was reported to contain 0.5 atoms of iron per 89 kDa subunit and to be completely inhibited by ethylenediaminetetraacetate (EDTA). However the present work shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 47 publications
3
50
0
Order By: Relevance
“…The UV-visible spectrum of recombinant HsQSOX1 shows a typical unresolved flavin envelope (Figure 4) that was seen for both the rat seminal vesicle (RnQSOX1), the avian egg white (GgQSOX1) and the bovine milk (BtQSOX1) enzymes (1,18,19). The experimentally-determined extinction coefficient is 12.5 ± 0.6 mM −1 cm −1 at 456 nm (see Methods), comparable to that obtained for GgQSOX1.…”
Section: Expression Of Human Qsox1 In Escherichia Colisupporting
confidence: 69%
“…The UV-visible spectrum of recombinant HsQSOX1 shows a typical unresolved flavin envelope (Figure 4) that was seen for both the rat seminal vesicle (RnQSOX1), the avian egg white (GgQSOX1) and the bovine milk (BtQSOX1) enzymes (1,18,19). The experimentally-determined extinction coefficient is 12.5 ± 0.6 mM −1 cm −1 at 456 nm (see Methods), comparable to that obtained for GgQSOX1.…”
Section: Expression Of Human Qsox1 In Escherichia Colisupporting
confidence: 69%
“…Although this monothiol is a poor substrate of both protist and mammalian QSOX enzymes (28,53,54), communication between GSH and the C I XXC II disulfide is rapid enough to ensure equilibration with the FAD after several sec- 24 and thus runs as a higher molecular weight band than the oxidized protein. Minor intermediate bands corresponding to protein containing a mixed disulfide species with glutathione (*) were excluded from analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Thiol Substrates-The trypanosomal enzyme (28), like other QSOXs (3,18,32,54), is capable of oxidizing a very wide range of mono-, di-, and multithiol substrates. Conformationally flexible peptides and proteins containing two or more cysteine residues appear to be excellent substrates of the enzyme, although there is comparatively little data regarding their redox potentials.…”
Section: Tbqsox In Thermodynamic Context: Redox Potentials Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 These clusters finally aggregate into larger and not active nanoparticles. The reaction mechanism has been theoretically studied and it is shown that isolated gold atoms cannot activate O 2 , while small gold clusters are excellent catalysts for O 2 activation and formation of disulfide.…”
mentioning
confidence: 99%